Hubungan penguasaan kosakata dan motivasi belajar dengan kemampuan menulis narasi kelas IV sekolah dasar - Refy Kusuma Wardani; Slamet Slamet; Joko Daryanto (Didaktika Dwija Indria, 2023)
This study aims to determine (1) whether there is a relationship between vocabulary mastery and narrative writing skills; 2) the relationship of learning motivation with the ability to write narration; (3) the relationship between vocabulary and learning motivational with the ability to write narration. The method used is the correlational method. The sample is 3 elementary schools, totaling 79 students. Data collection using tests and questionnaires. The ability to write variable narratives is used in the form of a composing test instrument, an instrument of learning motivation variable used in the form of a questionnaire, mastering the vocabulary of data variables obtained with choice test. Data were analyzed using inferential analysis of the F test and t test. The results showed that (1) there was a significant relationship between vocabulary mastery with the ability to write narrative tcount (317.66)> rtable (3.97), the correlation coefficient tested by t test, the results of tcount (17.33)> ttable (1.66); (2) there is significant the relationship between learning motivation and narrative writing ability price r count (37.43)> r table (3.97), the correlation coefficient is tested by t test, the tcount (7.40)> Table (1.66); (3) there is a significant correlation between vocabulary words and motivation to learn together with the ability to write narration. ry (1,2) equal to 0.94, the coefficient of significance with the F test obtained F count = 302.01, the real level á = 0, 05, with df 76 obtained Ftable = 3.12 then Fcount> Ftable. Thus, it can be concluded that mastery of vocabulary and learning motivation has significant relationship with students' ability to write narration.